Ilustrações do património natural do Concelho de Vouzela - Lopes, Ângela Isabel Pereira (2014)
Este trabalho consistiu na ilustração de espécies florísticas de interesse comunitário, desenhos de silhueta de árvores e arbustos e a ilustração de um habitat ripícola. Estas ilustrações foram realizadas para integrar um projecto já existente de inventário do património Natural do Concelho de Vouzela. Exceptuando a ilustração do habitat, as restantes foram realizadas para fazer parte de uma publicação da responsabilidade da Câmara Municipal de Vouzela. A ilustração do habitat ripícola, foi realizada com o intuito de promover e divulgar o património Natural do Concelho. Todas as ilustrações estão voltadas para espécies da flora da região, uma vez que é esse o principal foco do projecto em que se inserem, deixando de parte as espécies de fauna; ### Abstract: Illustrations of the natural heritage of Municipality of Vouzela This work was the illustration of floristic species of Community interest, drawings silhouette of trees and shrubs and the illustration of a riparian habitat. These illustrations were made to integrate an existing project inventory the natural heritage of the Municipality of Vouzela. Except illustration of habitat, the remaining were held to be part of a publication of the responsibility of the city council of Vouzela. Illustration of riparian habitat, was held in order to promote and disseminate the natural heritage of the county. All illustrations are focused on plant species of the region, since this is the main focus of the project to which they belong, leaving aside the animal species.